2007
DOI: 10.1021/ol0705649
|View full text |Cite
|
Sign up to set email alerts
|

Function-Oriented Synthesis:  Studies Aimed at the Synthesis and Mode of Action of 1α-Alkyldaphnane Analogues

Abstract: [reaction: see text] An efficient synthetic route to the ABC tricyclic core of 1alpha-alkyldaphnanes has been developed. The conformational bias imparted by the C6-C9 oxo-bridge of BC-ring system 12 was used to elaborate the ABC-ring system precursor including the introduction of the beta-C5 hydroxyl group. A completely diastereoselective palladium-catalyzed enyne cyclization was then employed to establish the A-ring with a C1 appendage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 22 publications
2
25
1
Order By: Relevance
“…49, 50 We have also conducted extensive investigations into the reaction mechanism and confirmed that the reaction occurs via a Claisen-type rearrangement in our cases 51, 52 rather than a 1,4-addition of the enol to the catalytically generated α,β -unsaturated acyl azolium. 53, 54 Furthermore, our elucidated mechanism suggested that the Claisen rearrangement on the hemiacetal intermediate ( II ) should be the stereochemically determining step.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…49, 50 We have also conducted extensive investigations into the reaction mechanism and confirmed that the reaction occurs via a Claisen-type rearrangement in our cases 51, 52 rather than a 1,4-addition of the enol to the catalytically generated α,β -unsaturated acyl azolium. 53, 54 Furthermore, our elucidated mechanism suggested that the Claisen rearrangement on the hemiacetal intermediate ( II ) should be the stereochemically determining step.…”
Section: Introductionsupporting
confidence: 69%
“…For example, Wender has established Claisen rearrangements of kojic acid as a useful synthetic platform for complex molecules synthesis but also noted the failure of traditional chiral Lewis acid approaches to the Claisen rearrangement of this particular substrate (Figure 1). 49 …”
Section: Resultsmentioning
confidence: 99%
“…The addition of excess ligand evidently competes substrate away from the Lewis acid. Interestingly, it was reported (in a footnote) 12 that a Zn(OTf) 2 pybox complex catalyzes the asymmetric Claisen rearrangement of a substituted allyl kojate in a 74:26 er , which is at odds with the observations here.…”
contrasting
confidence: 84%
“…This product was further converted into the ABC tricyclic daphnane core 108, opening the route to 1a-alkyldaphnanes. [72] This strategy was based on the key intramolecular [5 + 2] cycloaddition of pyranone 104, originally reported by the same authors in 1991. [73] In order to get insights into the mechanism of this type of reaction, several theoretical studies have been undertaken.…”
Section: Intramolecular [5 + 2] Cycloadditions Of Oxidopyrylium Ionsmentioning
confidence: 99%